Multi‐Site Functionalization of Protein Scaffolds for Bimetallic Nanoparticle Templating. (18th October 2014) - Huggins, Kelly N. L.; Schoen, Alia P.; Arunagirinathan, Manickam Adhimoolam; Heilshorn, Sarah C.
<x xml:space="preserve">Abstract</x> The use of biological scaffolds to template inorganic material offers a strategy to synthesize precise composite nanostructures of different sizes and shapes. Proteins are unique biological scaffolds that consist of multiple binding regions or epitope sites that site‐specifically associate with conserved amino acid sequences within protein‐binding partners. These binding regions can be exploited as synthesis sites for multiple inorganic species within the same protein scaffold, resulting in bimetallic inorganic nanostructures. This strategy is demonstrated with the scaffold protein clathrin, which self‐assembles into spherical cages. Specifically, tether peptides that noncovalently associate with distinct clathrin epitope sites, while initiating simultaneous synthesis of two inorganic species within the assembled clathrin protein cage, are designed. The flexibility and diversity of this unique biotemplating strategy is demonstrated by synthesizing two types of composite structures (silver–gold mixed bimetallic and silver–gold core–shell nanostructures) from a single clathrin template. This noncovalent, Template Engineering Through Epitope Recognition, or TEThER, strategy can be readily applied to any protein system with known epitope sites to template a variety of bimetallic structures without the need for chemical or genetic mutations.